Research proposals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A workshop on how to draft funding proposals for agricultural research was hosted by the Malagasy research centre FOFIFA in Antananarivo in December 1999. Attended by 12 specialists from Burundi, Congo (DR), Madagascar, and Rwanda, it followed hot...